Management of Oxidative Stress: Crosstalk Between Brown/Beige Adipose Tissues and Skeletal Muscles - Pan, Ruping; Chen, Yong (Frontiers in Physiology, 2021)
Exercise plays an important role in the physiology, often depending on its intensity, duration and frequency. It increases the production of reactive oxygen species (ROS). Meanwhile, it also increases antioxidant enzymes involved in the oxidative damage defense. Prolonged, acute or strenuous exercise often leads to an increased radical production and a subsequent oxidative stress in the skeletal muscles, while chronic regular or moderate exercise results in a decrease in oxidative stress. Notably, under pathological state, such as obesity, aging etc., ROS levels could be elevated in humans, which could be attenuated by proper exercise. Significantly, exercise stimulates the development of beige adipose tissue and potentially influence the function of brown adipose tissue (BAT), which are known to be conducive to a metabolic balance through non-shivering thermogenesis and may protect from oxidative stress. Exercise-related balance of the ROS levels is associated with a healthy metabolism in humans. In this review, we summarize the integrated effects of exercise on oxidative metabolism, and especially focus on the role of brown and beige adipose tissues in this process, providing more evidence and knowledge for a better management of exercise-induced oxidative stress.